2002
DOI: 10.2166/wst.2002.0587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aerobic and anoxic phosphorus uptake in ndbepr systems (uct and enbnras)

Abstract: Two Nitrification-Denitrification Biological Excess Phosphorus Removal (NDBEPR) systems have been operated for 8.5 months in order to compare their Biological Excess Phosphorus Removal (BEPR) performance. One of these systems, i.e. the University of Cape Town (UCT) system, exhibits mainly aerobic P uptake while the External Nitrification Biological Nutrient Removal Activated Sludge (ENBNRAS) system is characterised by high anoxic P uptake. It was observed that when operating with predominantly aerobic P uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In ENBNRAS systems, significant anoxic P uptake was observed (> 37%) with similar reductions in the ratios above, 1.1-2.8, 0.06-0.08 and 0.012-0.017 respectively, with f XBG,P in the range of 0.1-0.28 (Hu, 2001). By operating a UCT (conventional internal nitrification) BNRAS system in parallel with the external nitrification BNRAS system of Sotemann et al (2000), Vermande et al (2000) confirmed the reduced BEPR with significant anoxic/aerobic P uptake compared with that with predominantly aerobic P uptake.…”
Section: Bepr Behaviour In Systems With Anoxic P Uptakementioning
confidence: 68%
“…In ENBNRAS systems, significant anoxic P uptake was observed (> 37%) with similar reductions in the ratios above, 1.1-2.8, 0.06-0.08 and 0.012-0.017 respectively, with f XBG,P in the range of 0.1-0.28 (Hu, 2001). By operating a UCT (conventional internal nitrification) BNRAS system in parallel with the external nitrification BNRAS system of Sotemann et al (2000), Vermande et al (2000) confirmed the reduced BEPR with significant anoxic/aerobic P uptake compared with that with predominantly aerobic P uptake.…”
Section: Bepr Behaviour In Systems With Anoxic P Uptakementioning
confidence: 68%
“…This is confirmed in our investigation, but the ENBNRAS system does not have to stimulate anoxic P-uptake BEPR. In fact, it was observed that anoxic P-uptake BEPR is significantly lower (roughly two-thirds) compared with aerobic P-uptake BEPR for the same influent RBCOD concentration (Hu et al, 2002a(Hu et al, , 2002bVermande et al, 2002).…”
Section: Opportunities For Implementation Of Enbnras Systems and Systmentioning
confidence: 98%
“…This test was divided into two parts: (i) Anaerobic phosphorus release pretreatment: Previous researchers found that the phosphorus contained in the biomass could be released as soluble phosphate under anaerobic conditions, whereas uptake could occur under aerobic conditions. Further, prior anaero- [24,25]. Consequently, the biofilm was pretreated under anaerobic condition since it might be phosphate saturated after a period of operation.…”
Section: Examination Of the Biofilms Phosphorus Storage Capacitymentioning
confidence: 99%